2016
DOI: 10.1002/sce.21231
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Secondary School Students Lose Their Interest in Science? Or Does it Never Emerge? A Possible and Overlooked Explanation

Abstract: In this paper, we review research on how students' interest in science changes through the primary to secondary school transition. In the literature, the findings generally show that primary students enjoy science but come to lose interest during secondary school. As this claim is based mainly on interview and questionnaire data, that is on secondary reports from students about their interest in science, these results are reexamined through our own extensive material from primary and secondary school on how in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 34 publications
(78 reference statements)
0
32
0
9
Order By: Relevance
“…The percentage of female students who believed that men were better than women in mathematics jumped from 15% in ninth grade to 25% in 11th grade (Sansone, ). As argued by Anderhag et al (), education before high school often concerns everyday topics—interests that anyone could acquire in daily life—but, starting from high school, science education emphasizes scientific purposes that are gradually decontextualized from everyday interests. The majority of the students cannot spontaneously develop an appreciation for the scientific purpose behind science learning and often rely on school teachers to cultivate such an appreciation (Anderhag, Emanuelsson, Wickman, & Hamza, ; Carlone, Scott, & Lowder, ).…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of female students who believed that men were better than women in mathematics jumped from 15% in ninth grade to 25% in 11th grade (Sansone, ). As argued by Anderhag et al (), education before high school often concerns everyday topics—interests that anyone could acquire in daily life—but, starting from high school, science education emphasizes scientific purposes that are gradually decontextualized from everyday interests. The majority of the students cannot spontaneously develop an appreciation for the scientific purpose behind science learning and often rely on school teachers to cultivate such an appreciation (Anderhag, Emanuelsson, Wickman, & Hamza, ; Carlone, Scott, & Lowder, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence for a decline of interest over the years of schooling. Particularly, students tend to lose their interest in natural science subjects such as chemistry and physics (Anderhag et al, 2016;Krapp & Prenzel, 2011;Wigfield & Cambria, 2010). Krapp and Prenzel (2011) emphasize three main reasons for this decline, namely, (i) the quality and type of instruction (Kunter et al, 2014;Schiefele & Schaffner, 2015;Tr€ obst, Kleickmann, Lange-Schubert, Rothkopf, & M€ oller, 2016); (ii) developmental issues (students in adolescence prioritize new developmental tasks); and (iii) differentiation processes of interest in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Krapp and Prenzel (2011) emphasize three main reasons for this decline, namely, (i) the quality and type of instruction (Kunter et al, 2014;Schiefele & Schaffner, 2015;Tr€ obst, Kleickmann, Lange-Schubert, Rothkopf, & M€ oller, 2016); (ii) developmental issues (students in adolescence prioritize new developmental tasks); and (iii) differentiation processes of interest in adolescence. Additionally, findings by Anderhag et al (2016) indicate a change of students' object of interest in science subjects during their school life, from general enjoyment of being in class to an increasing focus on scientific objects, underlining the need for a more discriminated approach for assessing interest.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing PS and L-SS students has indicated that the latter are oriented more towards practical issues (e.g. nutrition, modern diseases or phenomenon that science cannot explain) than areas such as biology or technology in general (Jidesjö 2008;Anderhag et al 2016). Based on this, we assume that our observations are also influenced by the specificity of this age group.…”
Section: Discussionmentioning
confidence: 83%